Planning-Budgeting Consistency in Urban Tourism Governance: Evidence From Yogyakarta City - Hendrika Ayuliani Muntiyas; Izza Mafruhah; Suryanto; Nurul Istiqomah (Universitas Tidar, 2026)
This study aims to analyze the level of consistency between planning and budgeting of the tourism sector in Yogyakarta City by examining the relationship between vision, mission, programs, and budget allocation in various regional planning documents. Previous studies generally focus on program nomenclature similarity or the relationship between two planning documents, whereas this study evaluates consistency across planning horizons and across regional apparatus. The analysis was carried out through a consolidated approach of RPJPD, RPJMD, RKPD, RENSTRA, and DPA, as well as a comparison of budget values based on variance and percentage change between documents. The results shows that planning consistency at the level of strategic policies and programs, especially between RPJPD-RPJMD and RPJMD-RKPD, is in the very high category. However, in the budgeting aspect, significant deviations were found between the RPJMD, RKPD, and DPA, especially in tourism programs that are cross-sectoral and managed by more than one regional apparatus organization. Despite the numerical budget inconsistency, the performance of the tourism sector in Yogyakarta City showed achievements that exceeded the target, indicating the effectiveness of policy implementation and cross-sectoral support. These findings confirm that the consistency of planning and budgeting in the tourism sector is not solely determined by the nominal suitability of the budget, but by the quality of institutional coordination and policy integration across regional apparatus in the framework of sustainable tourism development.